Multi-Channel Seismic Shot Data from the Ross Sea seismic survey conducted during Palmer cruise NBP1502 (2015) ... - Bart, Philip (Interdisciplinary Earth Data Alliance (IEDA), 2019)
This data set was acquired with a portable Multi-Channel Seismic system during the 2015 Nathaniel B. Palmer cruise NBP1502 to the Ross Sea (chief scientists Philip Bart and John Anderson). The data files are in SEG-Y format and contain Multi-Channel Seismic Reflection shot data that has not been processed. The data set was acquired as part of the projects called (1) Timing and Duration of the LGM and Post-LGM Grounding Events in Whales Deep Paleo Ice Stream, Eastern Ross Sea Middle Continental Shelf and (2) Evidence for Paleo Ice Stream Collapse in the Western Ross Sea since the Last Glacial Maximum. Funding was provided by NSF grants PLR12-46357 and PLR12-46353. ...